(untitled) (TAJ: Journal of Teachers Association, 2009)
This is a prospective study carried out at the department of surgery, Dhaka Shishu Hospital during the period from 1st February 1997 to 28th February, 1999. Fifty peadiatiric patients aged less than 12 yrs with provisional diagnosis of intussusception were included in this study. Highest number of patients were within 1 year of age (70%), male female ratio was 2.57:1, the exact aetiology of intussusception could not be indentified in majority of the cases (90%). Abdominal pain (82%), vomiting (78%) and per rectal bleeding (62%) was common presentations. All patients were managed surgically. Ileocolic type was commonest type of intussusception (66%). Postoperative complications was noted in 14% cases. With limited resources, this study tried to collect many information about various aspect of intussusception in Bangladeshi children. It is hoped that organization and compilation of these information will stimulate further studies, leading to a greater comprehension of the problems of intussusception of paediatric age groups in our country. doi: 10.3329/taj.v18i2.3171 TAJ 2005; 18(2): 80-83